Importance of the Daily Light Cycle in Population–Habitat Relations: A Simulation Study. Issue 1 (8th January 2021) - Railsback, Steven F.; Harvey, Bret C.; Ayllón, Daniel
Abstract: Salmonids adaptively select when in the daily light cycle to feed, and they use different habitat at different times of day; however, the data and methods used to evaluate management actions like instream flows and restoration projects typically consider daytime only. Our new model, inSTREAM 7, lets us investigate how management decisions might change if we consider the full daily light cycle. The model explicitly represents the effects of light intensity on feeding efficiency, predation risk, and, therefore, foraging behavior. We simulated trout population response to a range of flows at restored and unrestored sites by using model versions that represented one (daytime only), two (day and night), and four (dawn, day, dusk, and night) light phases per day. Inclusion of night and crepuscular phases in the model produced important changes in results: it allowed model trout to convert improved growth conditions to increased survival by feeding less often during the day. This adaptive ability produced sharper population responses to habitat improvements. Crepuscular phases can be important because they let trout feed in the same higher‐velocity habitat used in daylight but with reduced predation risk. Analyses of parameter uncertainty and circadian cycles in food availability indicated that simulated population responses of management importance are not sensitive to details of how light affects feeding and predation risk. We suggest ways to consider night and crepuscular periods in management decision making and monitoring even without complex simulations.